PENGARUH BIOCHAR SEKAM PADI DAN TONGKOL JAGUNG TERHADAP PENURUNAN LOGAM Fe - Aulia Nur Mustaqiman; Ruslan Wirosoedarmo; Bambang Suharto (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
The potential for agricultural waste such as rice husks and corn cobs is very abundant and also can disturb the environment. However, this waste can be returned to agricultural land in the form of biochar or activated charcoal by means of pyrolysis using either low temperature or high temperature. Biochar is a byproduct of the thermochemical conversion of biomass which is recognized as a favorable soil amendment, which is introduced into the soil to increases groundwater retention in order to increases the saturated hydraulic conductivity of upper soil, affecting an aggregation, infiltration, and water capacity, decreasesing soil penetration resistance. Based on several previous studies, biochar can bind heavy metals contained in leachate, especially heavy metal Fe content. Utilization of leachate as an organic fertilizer which contains many nutrients essential for the growth of soybean plants. This research purposes to get the Fe-reduction influenced by biochar based on rice husk. The method used is to make biochar by pyrolysis process with low to high temperatures to obtain adsorption of heavy metals contained by leachate.